(1 point) By dragging statements from the left column to the right column below, give a proof by induction of the following statement: The correct proof will use 8 of the statements below. Statements to choose from: k(k + 1)(2k + 1) Then 12+22+... +k² = = Thus P(k) is true for all k. Now assume that P (k) is true for an arbitrary Integer k ≥ 1. So 12+22++(k+1)² k(k+1)(2k+1) +(k+1)² k(k+1)(2k+1)+(k+1)² = (k+1)((k+1)+ 1)(2(k + 1) + 1) = Let P(n) be the predicate, 12 +22+ +7 = n(n + 1)(2n+1), 6 Therefore, by the Principle of Mathematical Induction, P(n) is true for all n ≥ 1. Note that 12 KLX1+1)(2-1+1) 6 Thus P(k+1) is true. Then k(k+1)(2k+1) 12+2²++ ++(k+1)²= by the inductive hypothesis. Note that 12+22++(k+1)²= (12+22++k²)+(k+1)². Now assume that P(k + 1) is true for all k. Then we see that 12+2++(k+1)² = k(k+1)(2k+1) +(k+1)² k(k+1)(2k+1) 6(k+1)² + 6 6 2k3 + 3k² + k 6k² + 12k +6 = + 6 6 2k3 +9k2+13k+6 6 (k+1)(k+2)(2k+3) 6 (k+1)((k+1)+ 1)(2(k+1)+1) Your Proof: Put chosen statements in order in this column and press the Submit Answers button. For all n ≥ 1, 12+22+...+n² n(n + 1)(2n+1) = 6
(1 point) By dragging statements from the left column to the right column below, give a proof by induction of the following statement: The correct proof will use 8 of the statements below. Statements to choose from: k(k + 1)(2k + 1) Then 12+22+... +k² = = Thus P(k) is true for all k. Now assume that P (k) is true for an arbitrary Integer k ≥ 1. So 12+22++(k+1)² k(k+1)(2k+1) +(k+1)² k(k+1)(2k+1)+(k+1)² = (k+1)((k+1)+ 1)(2(k + 1) + 1) = Let P(n) be the predicate, 12 +22+ +7 = n(n + 1)(2n+1), 6 Therefore, by the Principle of Mathematical Induction, P(n) is true for all n ≥ 1. Note that 12 KLX1+1)(2-1+1) 6 Thus P(k+1) is true. Then k(k+1)(2k+1) 12+2²++ ++(k+1)²= by the inductive hypothesis. Note that 12+22++(k+1)²= (12+22++k²)+(k+1)². Now assume that P(k + 1) is true for all k. Then we see that 12+2++(k+1)² = k(k+1)(2k+1) +(k+1)² k(k+1)(2k+1) 6(k+1)² + 6 6 2k3 + 3k² + k 6k² + 12k +6 = + 6 6 2k3 +9k2+13k+6 6 (k+1)(k+2)(2k+3) 6 (k+1)((k+1)+ 1)(2(k+1)+1) Your Proof: Put chosen statements in order in this column and press the Submit Answers button. For all n ≥ 1, 12+22+...+n² n(n + 1)(2n+1) = 6
Advanced Engineering Mathematics
10th Edition
ISBN:9780470458365
Author:Erwin Kreyszig
Publisher:Erwin Kreyszig
Chapter2: Second-order Linear Odes
Section: Chapter Questions
Problem 1RQ
Related questions
Question
Don't use chat gpt It Chatgpt means downvote
![(1 point)
By dragging statements from the left column to the right column below, give a proof by induction of the following statement:
The correct proof will use 8 of the statements below.
Statements to choose from:
k(k + 1)(2k + 1)
Then 12+22+...
+k² =
=
Thus P(k) is true for all k.
Now assume that P (k) is true for an arbitrary
Integer k ≥ 1.
So
12+22++(k+1)²
k(k+1)(2k+1)
+(k+1)²
k(k+1)(2k+1)+(k+1)²
=
(k+1)((k+1)+ 1)(2(k + 1) + 1)
=
Let P(n) be the predicate,
12 +22+
+7
=
n(n + 1)(2n+1),
6
Therefore, by the Principle of Mathematical
Induction, P(n) is true for all n ≥ 1.
Note that 12
KLX1+1)(2-1+1)
6
Thus P(k+1) is true.
Then
k(k+1)(2k+1)
12+2²++
++(k+1)²=
by
the inductive hypothesis.
Note that 12+22++(k+1)²=
(12+22++k²)+(k+1)².
Now assume that P(k + 1) is true for all k.
Then we see that
12+2++(k+1)²
=
k(k+1)(2k+1)
+(k+1)²
k(k+1)(2k+1) 6(k+1)²
+
6
6
2k3 + 3k² + k
6k² + 12k +6
=
+
6
6
2k3 +9k2+13k+6
6
(k+1)(k+2)(2k+3)
6
(k+1)((k+1)+ 1)(2(k+1)+1)
Your Proof: Put chosen statements in order in this
column and press the Submit Answers button.
For all n ≥ 1, 12+22+...+n²
n(n + 1)(2n+1)
=
6](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2Fcd1647be-7894-4a41-b678-880b0af3a241%2Ff662155f-a395-4d90-81ee-dc87e738d657%2Fs0ojpyd_processed.jpeg&w=3840&q=75)
Transcribed Image Text:(1 point)
By dragging statements from the left column to the right column below, give a proof by induction of the following statement:
The correct proof will use 8 of the statements below.
Statements to choose from:
k(k + 1)(2k + 1)
Then 12+22+...
+k² =
=
Thus P(k) is true for all k.
Now assume that P (k) is true for an arbitrary
Integer k ≥ 1.
So
12+22++(k+1)²
k(k+1)(2k+1)
+(k+1)²
k(k+1)(2k+1)+(k+1)²
=
(k+1)((k+1)+ 1)(2(k + 1) + 1)
=
Let P(n) be the predicate,
12 +22+
+7
=
n(n + 1)(2n+1),
6
Therefore, by the Principle of Mathematical
Induction, P(n) is true for all n ≥ 1.
Note that 12
KLX1+1)(2-1+1)
6
Thus P(k+1) is true.
Then
k(k+1)(2k+1)
12+2²++
++(k+1)²=
by
the inductive hypothesis.
Note that 12+22++(k+1)²=
(12+22++k²)+(k+1)².
Now assume that P(k + 1) is true for all k.
Then we see that
12+2++(k+1)²
=
k(k+1)(2k+1)
+(k+1)²
k(k+1)(2k+1) 6(k+1)²
+
6
6
2k3 + 3k² + k
6k² + 12k +6
=
+
6
6
2k3 +9k2+13k+6
6
(k+1)(k+2)(2k+3)
6
(k+1)((k+1)+ 1)(2(k+1)+1)
Your Proof: Put chosen statements in order in this
column and press the Submit Answers button.
For all n ≥ 1, 12+22+...+n²
n(n + 1)(2n+1)
=
6
![](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2Fcd1647be-7894-4a41-b678-880b0af3a241%2Ff662155f-a395-4d90-81ee-dc87e738d657%2Ft8la7z_processed.jpeg&w=3840&q=75)
Expert Solution
![](/static/compass_v2/shared-icons/check-mark.png)
This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
Step by step
Solved in 2 steps with 2 images
![Blurred answer](/static/compass_v2/solution-images/blurred-answer.jpg)
Recommended textbooks for you
![Advanced Engineering Mathematics](https://www.bartleby.com/isbn_cover_images/9780470458365/9780470458365_smallCoverImage.gif)
Advanced Engineering Mathematics
Advanced Math
ISBN:
9780470458365
Author:
Erwin Kreyszig
Publisher:
Wiley, John & Sons, Incorporated
![Numerical Methods for Engineers](https://www.bartleby.com/isbn_cover_images/9780073397924/9780073397924_smallCoverImage.gif)
Numerical Methods for Engineers
Advanced Math
ISBN:
9780073397924
Author:
Steven C. Chapra Dr., Raymond P. Canale
Publisher:
McGraw-Hill Education
![Introductory Mathematics for Engineering Applicat…](https://www.bartleby.com/isbn_cover_images/9781118141809/9781118141809_smallCoverImage.gif)
Introductory Mathematics for Engineering Applicat…
Advanced Math
ISBN:
9781118141809
Author:
Nathan Klingbeil
Publisher:
WILEY
![Advanced Engineering Mathematics](https://www.bartleby.com/isbn_cover_images/9780470458365/9780470458365_smallCoverImage.gif)
Advanced Engineering Mathematics
Advanced Math
ISBN:
9780470458365
Author:
Erwin Kreyszig
Publisher:
Wiley, John & Sons, Incorporated
![Numerical Methods for Engineers](https://www.bartleby.com/isbn_cover_images/9780073397924/9780073397924_smallCoverImage.gif)
Numerical Methods for Engineers
Advanced Math
ISBN:
9780073397924
Author:
Steven C. Chapra Dr., Raymond P. Canale
Publisher:
McGraw-Hill Education
![Introductory Mathematics for Engineering Applicat…](https://www.bartleby.com/isbn_cover_images/9781118141809/9781118141809_smallCoverImage.gif)
Introductory Mathematics for Engineering Applicat…
Advanced Math
ISBN:
9781118141809
Author:
Nathan Klingbeil
Publisher:
WILEY
![Mathematics For Machine Technology](https://www.bartleby.com/isbn_cover_images/9781337798310/9781337798310_smallCoverImage.jpg)
Mathematics For Machine Technology
Advanced Math
ISBN:
9781337798310
Author:
Peterson, John.
Publisher:
Cengage Learning,
![Basic Technical Mathematics](https://www.bartleby.com/isbn_cover_images/9780134437705/9780134437705_smallCoverImage.gif)
![Topology](https://www.bartleby.com/isbn_cover_images/9780134689517/9780134689517_smallCoverImage.gif)